Estimation of cost for production of Aloe vera supplemented probiotic ice cream - Yadav, Vidhu; R.R.B., Singh; Hussain, Shaik Abdul (Indian Journal of Dairy Science, 2016)
The present study was performed to estimate production cost for Aloe vera supplemented probiotic ice cream (ASPIC). Ice cream with a combination of health enhancing ingredients viz. Aloe vera and probiotics can fill a gap in the market and fulfill consumer demand by providing a healthful solution to majority of the people with multiple health problems. Â The production conditions had been simulated and the production cost for the ASPIC was based on several assumptions with prime being 300 days of plant run and 500 kg ice cream mix per day. Various heads namely, land and building, plant and machinery, manpower, administration, utilities, raw material, manufacturing, packaging, marketing, logistics etc. were taken into account while estimating the expenditure for the production of the ice cream in a running plant. The final cost of production for ASPIC was estimated at Rs. 91.94 per litre.